PENGARUH KONSEP POLA GRID TERHADAP KEMAMPUAN JANGKAUAN LANSIA DI KELURAHAN KROBOKAN - Pratiwi, Busada Eka Kristi; Suprapti, Atiek; Murtini, Titien Woro (TEKNIK, 2013)
Elderly is people who aged 60 years and older and generaly has decreased physical and psychological. Thenumber of elderly in Kelurahan Krobokan has reached 8.9%, its means that the region can be said to havean old structure. Elderly in Kelurahan Krobokan can still use their environment can still use theirenvironment to get to a certain social facilities to meet their needs. Existing spatial pattern in the district isusing a grid that has a lot of intersections. The purpose of this study was to determine the physical aspects ofthe elements forming a regular grid patterns that exist in the area of research, so as to affect the nonphysicalaspects of the ability range of the elderly.Research methods that will be used is a qualitative method rationalistic. Where the assessment is used toform a grand theory of concept consisting of the variables that will be connected. Then the data analysisstarts from reviewing and systematics of data that has been obtained by grouping data into variables thathave been previously determined. The group is then presented in the form of maps, patterns, percentages andnarrative text. The data that has been arranged, then made a conclusion and interpretation.An analysis found that the grid pattern affect the ability of elderly to use their environment. The positiveinfluence that can reach the elderly Kelurahan Krobokan social facilities they want them to go the distanceeven beyond their ability.